Synthesis and Antifungal Activity of Isatin-3-semicarbazone - PANDEYA, S.N.; TRIPATHI, KISHU; KULSHRESHTHA, SHOBHA (Asian Journal of Chemistry, 2010)
Isatin-3-semicarbazone and substituted isatin-3-semicarbazone were synthesized and their antifungal activity was screened. It was observed that the semicarbazones showed inhibitory activity at 100-500 μg/mL.